2014
DOI: 10.1007/s10096-014-2176-x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of IFN-γ and IL-12 is associated with a milder form of hantavirus hemorrhagic fever with renal syndrome

Abstract: Hantavirus hemorrhagic fever with renal syndrome (HFRS) is a zoonotic disease characterized by acute onset, fever, malaise, and back pain. As the disease progresses, hemorrhagic disturbances and kidney dysfunctions predominate. The examination of tissue collected postmortem supports the premise that virus replication is not responsible for this pathology; therefore, it is widely believed that virus-induced immune responses lead to the clinical manifestations associated with HFRS. The overproduction of inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 53 publications
5
20
0
1
Order By: Relevance
“…Our data support previous observations that chemokines promoting mononuclear leukocyte migration are upregulated in hantavirus-infected patients (28). In this study, upregulation of CXCL9 and CXCL10 were characteristic for both HPS and HFRS throughout the course of the disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data support previous observations that chemokines promoting mononuclear leukocyte migration are upregulated in hantavirus-infected patients (28). In this study, upregulation of CXCL9 and CXCL10 were characteristic for both HPS and HFRS throughout the course of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Saksida et al demonstrated that the level of serum pro-inflammatory cytokines was higher in HFRS patients infected with Dobrava virus as compared to PUUV-infected patients (30). Additionally, our previous report points out the potential role of Th1-type immune response in the severity of NE (28). PUUV infection presents with a milder form of the disease and lower mortality rate when compared to Dobrava virus infections.…”
Section: Introductionmentioning
confidence: 92%
“…We have demonstrated that increased serum IFN- γ and IL-12 are associated with the mild form of NE [24]. These data confirm this observation, with a lower NE severity score being associated with higher levels of these cytokines.…”
Section: Discussionsupporting
confidence: 66%
“…Upregulation of these cytokines in female NE suggests that there is activation of Th1 lymphocytes. Previously, we have shown an association between the mild form of NE and elevated serum IFN- γ and IL-12 [24]. Therefore, these data suggest that lower severity scores in female cases are associated with activation of Th1 type immune response.…”
Section: Resultssupporting
confidence: 51%
“…Variations then depends on the phase and severity of the disease, with IFN-γ and IL-12 relating to mild forms [112]. An up-regulation of uPAR has also been described in PUUV patients.…”
Section: Activation Of Host Cell Factors By Hantavirusesmentioning
confidence: 99%